Open Ocular Injury with Corneal-Scleral Laceration and Lens Loss Due to Sharp Trauma in a Pediatric Patient - Rahmi, Amna; Priguna, Tangkas Mukti; Fitriyana, Nur Azizah; Mangando, Elcya Natalia Sanda (Journal of Community Health Provision, 2025)
Open Globe Injury (OGI) is common and can happen to anyone. Delayed treatment in children can lead to permanent blindness and reduce the child's quality of life. In this case, we inform about what was found and how it was treated. Case report: A 10-year-old girl complained of blurred vision, pain, and discharge from the right eye after being stabbed by a knife. The incident occurred 1 hour before the child was brought to the emergency room. Visual acuity in the right and left eyes was 1/~ with good light perception and 6/6, respectively. Soft palpation of the right eye during intraocular pressure (IOP) examination indicated decreased IOP. The results of the anterior segment examination of the right eye showed hyperemic conjunctiva, superior scleral laceration near the limbus, corneal laceration, shallow anterior chamber, brown iris with crypts, mid-dilated pupil, difficult to evaluate light reflex, and absent lens. The posterior segment of the right eye was difficult to evaluate. The Pediatric Penetrating Ocular Trauma Score (POTS) was 55. Initial management was performed in the ER and immediate cornea-sclera suturing surgery was performed, as well as iris claw lens placement was planned. The prognosis for the right eye was questionable. The outcome of OGI treatment varies from patient to patient. Appropriate and prompt treatment can prevent complications and improve the patient's visual outcome.